ONLINE EDUCATION: ADVANTAGES AND DISADVANTAGE AND SOLUTIONS (Archive of Conferences, 2021)
In the modern world, the winner is the one who has great knowledge. In order to know something, you need to learn. Now it is clear why so many people are trying to learn something new in order to keep up with the evolution. If you belong to this category of people who still want to learn, then you probably know what online lessons are. What is e-learning? E-learning (from English Electronic Learning, or simply e-Learning) is a system of learning using the Internet and electronic technologies. The bottom line is that the student uses gadgets to study and gain knowledge.